Developing country demand for crop germplasm conserved by the U.S. National Plant Germplasm System - Kelly Day Rubenstein; Paul W. Heisey (CABI Agriculture and Bioscience)
Abstract Background Future food production depends on the availability of crop varieties with more resistance to pests and diseases, temperature extremes, irregular moisture, and saltier soils. Plant breeders will need diverse germplasm to create improved varieties, especially in developing countries. The U.S. National Plant Germplasm System (NPGS) supplies germplasm to users worldwide. Methods To assess the demand for NPGS germplasm, we used: (1) distribution data from the Genetic Research Information Network; and (2) information collected directly from recipients of NPGS materials. Data collected included user characteristics, types of germplasm requested and received, the purpose of requests, the usefulness of materials received, and expectations for future use. Results For ten major crops, the NPGS distributed approximately 100,000 samples to users in developing countries during 2011–2015. NPGS germplasm ranged from final cultivars to crop wild relatives. These respondents requested proportionately more cultivars than are present in the NPGS. In developing countries, nearly all samples were received by scientists (98%). The most frequent purpose for requesting samples was basic research, followed by adding to collections, evaluating for specific traits, and breeding/prebreeding. These respondents found 38% of samples useful in breeding or in other ways. Another 38% of samples were still being evaluated. Previous research indicates the usefulness of samples is partially dependent on the data accompanying them. Compared with results from an earlier study, more samples had useful data. Finally, 64% of respondents in developing countries expected their use of the NPGS to increase, while only 8% expected their use to decrease. Conclusions The NPGS supplies significant amounts of crop germplasm to developing countries. The use of NPGS samples for basic research increased in developing countries. These respondents found more samples useful than those from an earlier study. NPGS samples were more likely to have useful data than in the past, which may enhance their usefulness. Finally, respondents in developing countries were more likely than other users to expect constant or increasing use of NPGS germplasm, underscoring the importance of NPGS materials for developing countries.